Digital humanities for green pedagogy: Embedding environmental sustainability (SDGs 4, 13) - Ahmed Abdel-Al Ibrahim, Khaled (Research Journal in Advanced Humanities, 2024)
This synthesis of forty studies examines the pivotal role of digital humanities (DH) tools in advancing green pedagogy and education for sustainable development. The research demonstrates how immersive technologies—including 3D virtual reality and digital mapping—alongside artificial intelligence platforms, digital storytelling, and gamification, are being leveraged to foster critical engagement with pressing environmental challenges. Across diverse educational contexts, from K-12 to postgraduate settings, educators and students utilize these tools through online platforms, participatory design, and project-based learning methodologies. The integration of DH tools with established pedagogical approaches like design thinking, participatory action research, and reflective practice proves highly effective. Reported outcomes include significant enhancements in digital literacy and sustainability awareness among learners, with some studies documenting measurable behavioral and cognitive shifts, such as a 12.6% reduction in resource consumption and a 28% increase in pro-environmental attitudes. The alignment of these initiatives with the United Nations Sustainable Development Goals (SDGs) is explicit, with thirty-two studies targeting Quality Education (SDG 4) and twenty-eight addressing Climate Action (SDG 13). By systematically mapping curricula to these global goals, the findings robustly position digital humanities not merely as a supplementary tool, but as a transformative methodology for enacting ecologically conscious and action-oriented learning.